A critical literature review on the link between multinational enterprises presence, absorptive capacity and competitive advantage of firms - Dishon, Wanjere Munuhe; Yabs, Dr. John (Archives of Business Research, 2017)
Scholars seem to agree on the importance of the local activity of foreign MNEs for country’s development, but opinions differ widely concerning their impact. As the government work out policies to improve Foreign Direct Investment, questions that need to be answered include how Multinational Enterprises affects the competitiveness of the local domestic enterprise. This paper presents a critical review of literature on the link between the presence of Multinational Enterprises, absorptive capacity and the competitiveness of domestic firms. A number of theories have been presented and empirical literature reviewed on the key constructs of the study. A conceptual model on the relationship was developed showing the link between MNEs presence, absorptive capacity and competitive advantage. Absorptive capacity was conceptualized as an intervening variable and was operationalised as research and development activities, internal and external organization of innovation and quality of human capital. This relationship was conceptualized as moderated by distance which was operationalised as culture, physical location and institutional difference. The competitiveness for the purpose of this study was conceptualized to mean productivity and innovation advantage. The reviewed literature confirms the fact that MNEs presence act as a source of knowledge which is transferred to domestic firms which in turn achieve competitive advantage. This transfer is made possible by the existence of the absorptive capacity among the firms. For that reason we emphasize that FDI related policy needs to be concerned not only with attracting MNEs, but also with securing effective benefits. In other words, policy makers must consider all factors that hinders knowledge transfer to the domestic firms like the absorptive capacity. The reviewed literature support the argument that the greater a firm’s exposure to knowledge sources, the greater the firm will acquire the competitive advantage. Like all research, the present study has limitations mainly the lack of primary data as it was more of a conceptual study.